Comparison of Disk Diffusion and Etest Methods to Determine the Susceptibility of Staphylococcus aureus Circulating in Riyadh, Saudi Arabia to Fusidic Acid - Ali M. Somily; David R. Peaper; Elijah Paintsil; Thomas S. Murray (International Journal of Microbiology)
Fusidic acid is a common therapy for staphylococcal infections in Saudi Arabia, but reports have suggested high rates of resistance among clinical isolates. Susceptibility testing of S. aureus to fusidic acid is further complicated by the lack of consensus on mean inhibitory concentrations (MIC) and disk diffusion cutoffs to determine resistance. The purpose of this study was to determine the correlation between disk diffusion and Etest determined MIC susceptibility results in clinical isolates of S. aureus from a large academic hospital in Riyadh, Saudi Arabia. Our data demonstrate excellent correlation between Etest determined MIC and disk diffusion susceptibility data, using either previously proposed zone sizes of ≥21 mm as susceptible and ≤18 mm as resistant or the EUCAST recommended zone size of ≤24 mm for resistance, in an area with relatively high rates of fusidic acid resistance.